GO/PEDOT:PSS nanocomposites: effect of different dispersing agents on rheological, thermal, wettability and electrochemical properties. (3rd April 2017) - Giuri, Antonella; Masi, Sofia; Colella, Silvia; Listorti, Andrea; Rizzo, Aurora; Liscio, Andrea; Treossi, Emanuele; Palermo, Vincenzo; Gigli, Giuseppe; Mele, Claudio; Esposito Corcione, Carola
Abstract: In this work glucose (G), α -cyclodextrin ( α -CD) and sodium salt of carboxymethyl cellulose (CMCNa) are used as dispersing agents for graphene oxide (GO), exploring the influence of both saccharide units and geometric/steric hindrance on the rheological, thermal, wettability and electrochemical properties of a GO/poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) nanocomposite. By acting on the saccharide-based additives, we can modulate the rheological, thermal, and wettability properties of the GO/PEDOT:PSS nanocomposite. Firstly, the influence of all the additives on the rheological behaviour of GO and PEDOT:PSS was investigated separately in order to understand the effect of the dispersing agent on both the components of the ternary nanocomposite, individually. Subsequently, steady shear and dynamic frequency tests were conducted on all the nanocomposite solutions, characterized by thermal, wettability and morphological analysis. Finally, the electrochemical properties of the GO/PEDOT composites with different dispersing agents for supercapacitors were investigated using cyclic voltammetry (CV). The CV results revealed that GO/PEDOT with glucose exhibited the highest specific capacitance among the systems investigated.